In vitro osteogenesis of rat adipose-derived stem cells: comparison with bone marrow stem cells - Kashani, Iraj Ragerdi; Zaminy, Arash; Barbarestani, Mohammad; Hedayatpour, Azim; Mahmoudi, Reza; Vardasbi, Safoura; Nejad, Ahmadreza Farzaneh; Naraghi, Mohammad ali (Archives of Medical Science, 2009)
Introduction: Adipose-derived stem cells (ADSCs) have been shown to differentiate into osteoblasts, adipocytes or myoblasts. However, it is not certain that ADSCs are equal to bone marrow stem cells (BMSCs) in their osteogenic differentiation potential. The purpose of this study was to answer the question. Material and methods: Mesenchymal stem cells (MSCs) were isolated from bone marrow and fat of adult rats. After cell expansion in culture media and three passages, osteogenesis was induced on a monolayer culture with osteogenic medium containing dexamethasone, b-glycerophosphate and ascorbate. After 4 weeks, expression of the osteocalcin gene was analyzed by RT-PCR, alkaline phosphatase (ALP) activity assayed, and Alizarin Red S and Von Kossa staining were done. Cell viability and apoptosis were also assayed by MTT and flow cytometry, respectively. Results: In the test of osteogenesis, the osteoblastic differentiation of ADSCs as demonstrated by ALP activity was less than that of the BMSCs. The amount of matrix mineralization shown by Alizarin Red S and Von Kossa staining also showed statistical differences between the two MSCs. The incidence of apoptotic cells among ADSCs was higher than BMSCs. The flow cytometry proves that cell growth reduction is due to a decrease of the cells entering the S phase of the cell cycle. The data demonstrated by MTT assay indicated that viable cells among ADSCs were lower than BMSCs in control groups. Conclusions: The results of our study suggest that ADSCs may have an inferior potential for osteogenesis compared with BMSCs.